Analysis of a Decade of Sustainable Tourism in Indonesia: Bibliometric Approach 2012 to 2022 - Indra Ratna Sari (JURNAL AKADEMISI VOKASI, 2024)
This journal reviews bibliometric analysis of sustainable tourism in Indonesia. This writing is motivated by the rise of tourist destinations in Indonesia that have implemented sustainable tourism. The aim of this journal is to determine changes in research regarding sustainable tourism in Indonesia based on bibliometric analysis. Bibliometric analysis in this journal includes document type, document source, document publication year, total citations for each document, and keyword network mapping using Vos Viewer software. The topics in this journal are the main keywords for data searches via Scopus. Bibliometric analysis was used to analyze 360 ​​of 511 documents published in the Scopus database in 2012 – 2022. The software used to assist bibliometric analysis is Harzing's Publis or Perish to find out the citation matrix and Vos Viewer to help with document mapping. The results show that the year with the highest total publications is 2021 and articles are the documents that dominate the data on this topic. The country with the most total publications is Indonesia because this journal focuses more on sustainable tourism in Indonesia. keywords: Bibliometric Analysis; Scientometrics; Sustainable Tourism in Indonesia; VoS Viewer